A Compton scattering setup for pulse shape discrimination studies in germanium detectors. (July 2017) - von Sturm, K.; Belogurov, S.; Brugnera, R.; Garfagnini, A.; Lippi, I.; Modenese, L.; Rosso, D.; Turcato, M.
Abstract: Pulse shape discrimination is an important handle to improve sensitivity in low background experiments. A dedicated setup was built to investigate the response of high-purity germanium detectors to single Compton scattered events. Using properly collimated γ -ray sources, it is possible to select events with known interaction location. The aim is to correlate the position dependent signal shape with geometrical and electrical properties of the detector. We report on design and performance of the setup with a first look on data. Abstract : Highlights: Automatized setup for the signal characterization of a HPGe detector depending on interaction location and bias voltage. Compton coincidence measurements with a Broad Energy Germanium (BEGe) detector. Single site event selection with known interaction location and high purity.